Increased HLA-DR and decreased CD3 on human intestinal intraepithelial lymphocytes: evidence of activation? - KELLEHER, DERMOT P; O'FARRELLY, CLIONA (BMJ, 1996)
BACKGROUND: Activation of circulating T lymphocytes results in expression of HLA-DR, interleukin-2 receptor (IL-2R), transferrin receptor (TrR), and decreased amounts of surface CD3. AIM: To examine the activation status of human intestinal intraepithelial lymphocytes (IELs) by flow cytometry. PATIENTS AND METHODS: Duodenal biopsy specimens from 12 patients provided a source of intestinal lymphocytes. Dual colour analysis was used to compare activation marker expression by IELs with peripheral blood (PB) T lymphocytes from the same patients. RESULTS: All human IEL populations express HLA-DR and their density of expression is lower than on the small population of HLA-DR+ resting PB T lymphocytes (mean fluorescence intensity (MFI) 52.9, range 19.8-94.8 v 152.6 range, 49.1-320.3; p < 0.01). The density of CD3 was significantly reduced on IELs (MFI 465.8, range 228.7-660), compared with PB T lymphocytes (756.3, range 444.5-1573.7; p < 0.009). IL-2R was not detected on IELs; nor were the activation markers, TrR, M21 C5, or M2 B3. CONCLUSION: HLA-DR expression on IELs together with decreased CD3 expression suggest previous stimulation. However, the absence of additional markers of T cell activation may reflect a unique pathway of activation.
PUBLISHED
Keywords: Biochemistry